Correction: Small Intestine Bacterial Overgrowth is associated with increased Campylobacter and epithelial injury in duodenal biopsies of Bangladeshi children. - PLOS Neglected Tropical Diseases Staff (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0012023.].